2019
DOI: 10.1021/acs.est.9b00218
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Polar Phenolic Disinfection Byproducts Are High-Affinity Human Transthyretin Disruptors: An in Vitro and in Silico Study

Abstract: Phenolic disinfection byproducts (phenolic-DBPs) have been identified in recent years. However, the toxicity data for phenolic-DBPs are scarce, hampering their risk assessment and the development of regulations on the acceptable concentration of phenolic-DBPs in water. In this study, the binding potency and underlying interaction mechanism between human transthyretin (hTTR) and five groups of representative phenolic-DBPs (2,4,6-trihalo-phenols, 2,6-dihalo-4-nitrophenols, 3,5-dihalo-4-hydroxybenzaldehydes, 3,5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 72 publications
1
37
0
Order By: Relevance
“…hTTR is the major carrier protein of THs across the placenta and the blood-brain barrier, and so the disruption of its transport processes may bring pollutants to normally inaccessible sites and induce deleterious health effects. This study confirmed that the most potent hTTR binders, with a binding affinity similar to that of T4, were at the same time aromatic, hydroxylated, and halogenated chemicals, able to give hydrogen bonding, electrostatic, and hydrophobic interactions with this protein [11].…”
Section: Role Of Noncovalent Interactions In Ed Recognitionsupporting
confidence: 74%
See 1 more Smart Citation
“…hTTR is the major carrier protein of THs across the placenta and the blood-brain barrier, and so the disruption of its transport processes may bring pollutants to normally inaccessible sites and induce deleterious health effects. This study confirmed that the most potent hTTR binders, with a binding affinity similar to that of T4, were at the same time aromatic, hydroxylated, and halogenated chemicals, able to give hydrogen bonding, electrostatic, and hydrophobic interactions with this protein [11].…”
Section: Role Of Noncovalent Interactions In Ed Recognitionsupporting
confidence: 74%
“…Disinfection byproducts are another group of derivatives that may bind to various human serum proteins. Such byproducts are formed by the reaction of disinfectants used for water treatment (like chlorine, chlorine dioxide, chloramine, or ozone) with natural organic matter and mostly consist of halogenated phenols, benzaldehydes, or benzoic acids [11]. Selected representative molecular structures and main application fields or sources of EDCs are reported in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…A data set containing 414 compounds with 560 hTTR binding affinity data was collected. ,,,, After careful data analysis, we found that there were seven compounds with an equal number of inconsistent data, which may result in failing to group them as an hTTR disruptor or not. Thus, they were erased from the final data set.…”
Section: Methodsmentioning
confidence: 99%
“… Among the available models, the applicability domain of most models was suitable only for limited groups of compounds, such as poly/perfluorinated compounds and brominated flame retardants. In the past three years, the hTTR binding affinity data of several new groups of substances, such as 2,6-dihalo-4-nitrophenols, 3,5-dihalo-4-hydroxybenzaldehydes, halosalicylic acids, halo-benzoic acids, halo-benzenesulfonic and halo-phenylboronic acids, tetrabromobisphenol A monoether structural analogs, bisphenols, and so on, were tested. , Further modeling action is expected to extend the applicability domain of predictive models by introducing more, new, tested compounds with structural diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis results indicated that 70 DBPs have been proven to have estrogenic activity, i.e., they can interfere with ER. There is evidence in toxicological and epidemiological research in cell cultures that haloacetonitriles (HANs), e.g., dibromoacetonitrile (DBAN) and 2,3-dibromopropionitrile (DBPN), can invoke adverse effects on the endocrine system by binding to the human estrogen receptor and androgen receptor [50,67]. Additionally, Nakamura et al [68] reported that halogenated derivatives of E1, E2, E3, and EE2 showed estrogenic activity, interfering with estrogen receptor α, using yeast two-hybrid assays between human and medaka fish (Oryzias latipes), The androgen hormone regulates the androgen signaling pathway via binding with the androgen receptor (AR), and it plays an essential role in the physiological processes of human development and reproduction [92].…”
Section: Hormone Receptor-mediated Mechanism Of Endocrine Disruptionmentioning
confidence: 99%